2015
DOI: 10.1186/s12966-015-0319-9
|View full text |Cite
|
Sign up to set email alerts
|

Reds are more important than greens: how UK supermarket shoppers use the different information on a traffic light nutrition label in a choice experiment

Abstract: BackgroundColour coded front-of-pack nutrition labelling (‘traffic light labelling’) has been recommended for use in the UK since 2006. The voluntary scheme is used by all the major retailers and some manufacturers. It is not clear how consumers use these labels to make a single decision about the relative healthiness of foods. Our research questions were: Which of the four nutrients on UK traffic light labels (total fat, saturated fat, sugar and salt) has the most influence on decisions? Do green lights or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 27 publications
7
58
2
2
Order By: Relevance
“…Thirdly, the study findings support previous research showing that consumers frequently have negative associations towards certain nutrient groups which they regard as unhealthy, and that they are avoiding certain groups more than they seek others in what might be a 'negativity bias' (Rozin & Royzman, 2001;Scarborough et al, 2015). In accordance with Song and Swartz (2009), consumers perceived ingredients as more risky when they were not familiar with the ingredient.…”
Section: Discussionsupporting
confidence: 88%
“…Thirdly, the study findings support previous research showing that consumers frequently have negative associations towards certain nutrient groups which they regard as unhealthy, and that they are avoiding certain groups more than they seek others in what might be a 'negativity bias' (Rozin & Royzman, 2001;Scarborough et al, 2015). In accordance with Song and Swartz (2009), consumers perceived ingredients as more risky when they were not familiar with the ingredient.…”
Section: Discussionsupporting
confidence: 88%
“…The traffic light and 'high in' warning INRS also ranked significantly higher for providing nutritional information that participants can use and for understanding the nutrient levels in comparison to that of the star rating app but did not differ with the ranking of the control (NFt). These findings are similar to those of previous research conducted in USA, UK, or Chile, where consumers indicated higher preference for nutrient specific systems, such as traffic light labels or 'high in' warning labels in comparison to a summary INRS system or control [52,[62][63][64][65][66][67][68][69][70]. For example, a web-based survey simulating an online grocery store, administered to 1182 people in Chile, indicated improved participants' ability to perform a healthful food purchase when randomized to FOP nutrition information (modified traffic light system or the Chilean warning system) in comparison to the control condition [52].…”
Section: Discussionsupporting
confidence: 89%
“…Research from USA have shown multiple traffic lights to perform better in comparison to other INRS (including a graded system, star ranking and a nutrition facts table-based approach) in helping consumers to identify the healthier products as well as understanding of the nutrient levels [71]. Data from the UK also indicated that the majority of consumers used multiple traffic lights to 'avoid red lights' similar to a high in warning FOP system [70]. Results from the present work are similar to other studies which did not find differences in consumer perceptions between the traffic light and 'high in' warning labels [19,52], likely because both are nutrient specific systems that communicate information about key nutrients (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When used in the context of food, the colour red can implicitly evoke an avoidance reaction, regardless of actual healthiness [49]. Similarly, research on the Multiple Traffic Light indicates that consumers are strongly driven to avoid red lights (more so than to select green lights) [50,51,52]. This negative colour association combined with a lack of familiarity with the Health Star Rating could have contributed to participants forming an overall negative impression of all products (healthy and unhealthy) with a Health Star Rating in that study [1].…”
Section: Front-of-pack Labelsmentioning
confidence: 99%